Analisis Kemampuan Dinamis dalam Kelangsungan Hidup Usaha Kecil di Ekosistem Kewirausahaan selama Covid-19 - Esy Nur Aisyah; Sudarmiatin Sudarmiatin; Agus Hermawan (IQTISHODUNA, 2022)
This research adopts a dynamic capability lens to study how small business entrepreneurs try to survive and grow in the entrepreneurial ecosystem affected by covid-19. The research method is using a qualitative design, 5 MSMEs in Malang City have been interviewed to assess how the entrepreneurial ecosystem in Malang City has been affected by covid-19. This allows a contemporary and realistic understanding of how small entrepreneurs are adapting to crises. The findings suggest that the entrepreneurs in this study can leverage their capabilities in terms of how they scan the current business environment and make decisions accordingly. Furthermore, small business entrepreneurs adopt a flexible approach to be able to react to the unexpected changes of covid-19 and the affected market environment. Business agility will help entrepreneurs to respond to internal and external changes in an efficient manner. Many business functions cannot resume due to the covid-19 pandemic. Marketing techniques that were considered profitable and successful before 2020 will not develop now. This is because small businesses work with fewer resources and are under financial pressure. To get the most out of fewer resources is to adapt to more digital-based functions.